Use of psychedelic treatments in psychiatric clinical practice: an EPA policy paper - Destoop, M; Mohr, P; Butlen, F; Kéri, P; Samochowiec, J; De Picker, L; Fiorillo, A; Kuypers, K P C; Dom, G (European psychiatry, 2025)
BACKGROUND: Recent years show an exponential increased interest ("renaissance") in the use of psychedelics for the treatment of mental disorders and broader. Some of these treatments, such as psilocybin for depression, are in the process of formal regulation by regulatory bodies in the US (FDA) and Europe (EMA), and as such on the brink of real-world implementation. In the slipstream of these developments increasing commercial initiatives are taking shape. The European Psychiatric Association (EPA) acknowledges both the therapeutic potential of psychedelic substances and the challenges for both research and clinical implementation. Steps need to be taken toward a well-balanced policy based upon sound scientific evidence and research, aiming at safe, ethical responsible integration of psychedelic therapy available for all patients who can potentially benefit. METHODS: In this EPA policy paper, we highlight the potential benefits, and also the challenges of psychedelic treatments, which can be relevant for the future real-world implementation of these treatments. RESULTS: In addition to an overview of the current evidence and hypotheses of working mechanisms of psychedelic treatment, this policy paper specifically highlights the importance of the psychosocial components of the treatment as well as the ethical and professional aspects playing a role in real-world implementation. CONCLUSIONS: Four recommendations are formulated for further research and clinical implementation.
Keywords: Hallucinogens; Evropa; Europe; halucinogeny; DMT; mental health; psychiatrie; psilocybin; Psychiatry; lidé; Psychedelics; methodological challenges; LSD; Humans; Mental Disorders; duševní poruchy; psychiatric disorders; Psilocybin